Risk Factors Leading to Mental Illness among Patients: A Retrospective Study (Indian Journal of Public Health Research & Development, 2020)
Background: Mental disorder is a psychological factor reflected in the behavior, which affect the normaldevelopment of a person’s culture. The burden of mental health problems is increasing globally. Most mentaldisorders are result of a combination of several different factors rather than just a single factor. Knowing therisk factors leading to mental illness, may help in future to reduce the incidences of mental illness by takingpossible preventive measures.Aim: The main aim of this study was to determine the risk factors leading to mental illness among patients.Materials and Method: Case control study design with quantitative non experimental descriptive surveyapproach was used .Mini mental status examination tool was used to select 100 psychiatric patients based oninclusion criteria and 100 general populations to find the odds ratio. Data was collected using a demographicproforma and risk factors assessment check list.Results: In biological, socioeconomic, environmental, psychological and personal factors, the highest valueof the odds ratio of risk factors for mental illness is sleep disturbance (16.385), financial problems (3.149),slum area (3.162), feeling of loneliness (13.821) and chronic smoking (16.116) respectively; it is higheramong patient with mental illness compared to the general population.Conclusion: Most of the subjects are having one or other risk factors for developing mental illness. Hencewe need to take care about risk factors and maintain good lifestyle to promote optimal mental health.
Keywords: Risk factors of mental illness; psychiatric patients; general population; retrospective study.